Significance of druggable targets (PD-L1, KRAS, BRAF, PIK3CA, MSI, and HPV) on curatively resected esophageal squamous cell carcinoma - Hong Kyu Lee; Mi Jung Kwon; Yong Joon Ra; Hee Sung Lee; Hyoung Soo Kim; Eun Sook Nam; Seong Jin Cho; Hye-Rim Park; Soo Kee Min; Jinwon Seo; Ji-Young Choe; Kyueng-Whan Min; et al. (BMC, 2020)
Abstract Background Esophageal squamous cell carcinoma (ESCC) still remains intractable disease with few therapeutic options. Programmed death-ligand 1 (PD-L1), which is essential for immune evasion, is involved in the pathogenesis of ESCC and thus is a potential therapeutic target. PIK3CA, KRAS, and BRAF mutations, microsatellite instability (MSI) caused by deficient mismatch repair (dMMR), and human papillomavirus (HPV) can potentially upregulate PD-L1 expression, which might contribute to the clinical outcome of patients with ESCC. Methods We investigated the significance of the present druggable markers [PD-L1, PIK3CA, KRAS, and BRAF mutations, MSI caused by deficient dMMR, and HPV] in 64 curatively resected ESCCs, using immunohistochemistry (PD-L1 and MMR protein expression), direct sequencing (KRAS, BRAF, and PIK3CA mutations), real-time PCR (HPV infection), and MSI using quasi-monomorphic markers. Results PD-L1 expression, PIK3CA mutation, and MSI/dMMR were detected in 35.9, 12.5, and 17.2% of ESCCs, respectively. HPV was rarely detected (1.6%) (high-risk HPV68), whereas KRAS and BRAF mutations were not detected in ESCCs. PD-L1-positive tumors were not correlated with PIK3CA mutation or MSI/dMMR (all P > 0.05). PD-L1, PIK3CA mutation, and MSI/dMMR characterized the patients associated with light smoking, female and younger age, and younger age and well-differentiated tumors, respectively (all P < 0.05). In multivariate analysis, only PD-L1-positivity was an independent favorable prognostic factor for overall survival (OS) and disease-free survival (DFS) (P = 0.023, P = 0.014). In the PD-L1-negative ESCCs, PIK3CA mutation had a poor prognostic impact on both OS and DFS (P = 0.006, P = 0.002). Conclusions PIK3CA mutation may be an alternative prognostic biomarker in PD-L1-negative curatively resected ESCCs that can be optional to identify high-risk patients with worse clinical outcome who require more intensive therapy and follow-up.